Determination of Ramipril and its Active Metabolite Ramiprilat from Plasma by Liquid Chromatography-Mass Spectrometry for Bioequivalence Studies - R. More, Abhijit; Vaidya, A.J.; Vaidya, V.V.; Deshmukh, R.G. (Asian Journal of Chemistry, 2010)
Ramipril and ramiprilat were isolated by solid phase extraction using PROSPEKT-2, which is an online solid phase extractor. This method is suitable for bioequivalence studies following single dose in healthy volunteers. This assay achieved higher sensitivity and better specificity for the analysis of ramipril and ramiprilat in human plasma. The limit of quantitation of 0.25 ng/mL for ramipril and ramiprilat was thus attainable by high performance liquid chromatography mass spectrometry (HPLC-MS/MS). The internal standard proved to be a good internal standard for this assay. No significant interference caused by endogenous compounds was observed. This simple and rapid assay can be successfully used in pharmacokinetic studies of ramipril and ramiprilat.